"The Dog Stole the Picture": The Hound of the Baskervilles and the Cinematic Revisionist Cycle of the 1970s and 1980s. Issue 2 (3rd April 2017) - Jones, Stephanie
ABSTRACT: Paul Morrissey's The Hound of the Baskervilles (1978) is a rare example of a cinematic Holmes adaptation that has very few advocates of its merits. It is cowritten by two legends of British comedy, Peter Cook and Dudley Moore, who appear alongside a who's who of British character acting. 1978's The Hound also marks the "nadir" of a cycle of "revisionist" Holmes adaptations (Nollen 194). This cycle parodied and critiqued Holmes. As Dan Harries has argued, the film parody became more mainstream and offered up ever more standardized discursive shifts (22). This article argues that The Hound 's critical reputation points to the film's tendency to buck the trend for standardization, offering a uniquely disruptive critique of Holmes.